Situational Script Management of Business Processes with Changeable Structure - Chaliy, S.; Chala, O. (My University, 2008)
In the presented work the problem of management business-processes with changeable structure is considered and situational based approach to its decision is offered. The approach is based on situational model of management business-process according to which process is represented as a set of situations. The script defining necessary actions is connected with each situation. Management of processes is carried out by means of the rules formalizing functional requirements to processes.
Keywords: Business-process; situational management; rules; procedures; roles